IMPLEMENTATION OF HYGIENE AND SANITATION IN KUSUMA KARTIKA SARI HOTEL SURAKARTA - Iwan Suryadi; Seviana Rinawati; Siti Rachmawati (Journal of Industrial Hygiene and Occupational Health, 2018)
The hospitality industry is one of the tourism facilities that play an important to increasing tourism revenues, but has risks as a place of transmission and spread of disease. This aims of study to provide an overview of the application of hygiene and sanitation at the Hotel Kusuma Kartika Sari Surakarta (Hotel KKS) by referring to Permenkes. 80 of 1990 on hotel health requirements and Decree of the Director General of PPM and PLP no. 95 of the year 1991 on the assessment of the Hotel Health Check. The research method is descriptive with interview technique and direct observation using hotel health inspection questionnaire. The result of research shows that Hotel KKS was in the healthy category based on hygiene and sanitation assessment calculation with presentation of 79%. The conclusion of this research is that the application of sanitation of Hotel KKS met the requirements of Hygiene and sanitation but for the environmental requirements variable it is still possible to enter and multiply the disease vector and annoying animal. In the room and space requirement variables there is no separation of male and female rest room and unavailability of locker for employees, goods in unorganized warehouse and height of shelf below 20 cm. On the variables of health requirements and sanitation facilities that the bathroom has not met the minimum amount in accordance with the number of employees and waste bins that still allow the proliferation of disease vectors and insects. Based on these results the hotel is expected to maintain the variables that have been qualified and improve the requirements that have not been met. Keywords: Hygiene, Hospitality Sanitation